A locally stabilized explicit approach for coupled thermo-mechanical analysis. (November 2020) - Soares, Delfim
Highlights: An effective novel approach is proposed to analyse thermo-mechanical models. The method is very efficient, enabling decoupled solutions and reduced solver efforts. It is locally defined, introducing modified elements to guarantee stability. It stands as an entirely automated, space/time self-adaptive procedure. Abstract: In this paper, a stabilized, locally defined, explicit approach is considered to analyse coupled thermo-mechanical models. In this sense, modified central and forward difference methods are adaptively applied following the features of the discretized model; thus, a connected formulation between the adopted temporal and spatial solution procedures takes place. The proposed technique enables stabilized decoupled analyses, allowing each "phase" of the coupled model to be handled separately, without considering stability restrictions for their time solutions, providing a very versatile and efficient methodology. In addition, the new formulation is designed as a single-solve framework based on reduced systems of equations, which further greatly improves the efficiency of the method. The new technique is accurate, simple to implement and entirely automated, requiring no decision or expertise from the user. Numerical results are presented at the end of the manuscript, illustrating the performance and effectiveness of the new procedure.